Evaluation of a European-wide survey on paediatric endoscopy training. Issue 2 (7th September 2018) - Broekaert, Ilse Julia; Jahnel, Joerg; Moes, Nicolette; van der Doef, Hubert; Ernst, Angela; Amil Dias, Jorge; Thomson, Mike; Tzivinikos, Christos
Abstract : Objective: To evaluate quality of paediatric endoscopy training of Young members of the European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN). Methods: An online questionnaire designed by the Young ESPGHAN Committee was sent to 125 Young ESPGHAN members between February 2014 and September 2015. The questionnaire comprised 32 questions addressing some general information of the participants and the structure of their paediatric gastroenterology, hepatology and nutrition programmes; procedural volume and terminal ileal intubation (TII) rate; supervision, assessments, participation in endoscopy courses and simulator training; and satisfaction with endoscopy training and self-perceived competency. Results: Of 68 participants, 48 (71%) were enrolled in an official training programme. All alumni (n=31) were trained in endoscopy. They completed a median of 200 oesophagogastroduodenoscopies (OGDs) and 75 ileocolonoscopies (ICs) with a TII rate of >90% in 43%. There is a significant difference in numbers of ICs between the TII rate groups >90%, 50%–90% and <50% (median 150 vs 38 vs 55) (p<0.001). 11 alumni (35%) followed the ESPGHAN Syllabus during training. 25 alumni (81%) attended basic skills endoscopy courses and 19 (61%) experienced simulator training. 71% of the alumni were '(very) satisfied' with their diagnostic OGD, while 52% were '(very) satisfied' with their IC training. The alumni felt safe to independently perform OGDs in 84% and ICs in 71% after their training. Conclusions: Despite reaching the suggested procedural endoscopy volumes, a rather low TII rate of >90% calls for end-of-training certifications based on the achievement of milestones of competency.